An integrated analysis of prognostic mRNA signature in early- and progressive-stage gastric adenocarcinoma - Hong, Xiaoling; Zhuang, Kai; Xu, Na; Wang, Jiang; Liu, Yong; Tang, Siqi; Zhao, Junzhang; Huang, Zunnan (Frontiers in Molecular Biosciences, 2023)
The pathogenesis and vital factors of early- and progressive-stage of stomach adenocarcinoma (STAD) has not been fully elucidated. In order to discover novel and potential targets to guide effective treatment strategies, a comprehensive bioinformatics study was performed, and the representative results were then validated by quantitative polymerase chain reaction (qPCR) and Immunohistochemical (IMC) staining in clinical samples. 4627, 4715 and 3465 different expression genes (DEGs) from overall-, early-, and progressive- stages STAD were identified respectively. Prognostic models of 5-year OS were established for overall-, early- and progressive- stages STAD, and ROC curves demonstrated AUC values for each model were 0.73, 0.87, and 0.92, respectively. Function analysis revealed that mRNAs of early-stage STAD were enriched in chemical stimulus-related pathways, whereas remarkable enrichment of mRNAs in progressive-stage STAD mainly lay in immune-related pathways. Both qPCR and IHC data confirmed the up-regulation of IGFBP1 in the early-stage and CHAF1A in the progressive-stage of STAD compared with their matched normal tissues, indicating that these two representative targets could be used to predict the prognostic status of the patients in these two distinct STAD stages, respectively. In addition, seven mRNAs (F2, GRID2, TF, APOB, KIF18B, INCENP and GCG) could be potential novel biomarkers for STAD at different stages from this study. These results contributed to identifying STAD patients at high-risk, thus guiding targeted treatment with efficacy in these patients.